Views on the TRIPS Agreement to find an approach to increase the access to pharmaceutical products in developing countries : a need for transforming the global medicine regime? - Wallden, Tiia (My University, 2021)
Lack of access to pharmaceutical products in developing countries is major problem due to strict patent protection. The aim of the thesis is to find out whether one of the suggested approaches could increase the access to pharmaceutical products by analyzing the TRIPS Agreement and discussing few ways to view it. The views are from the perspectives of public health, right to health as well as generic medicines. The analyzed approaches are the Medicine Patent Pool, Open-Source model and Orphan medicines. An analysis of whether the global medicine regime needs transforming will be discussed before concluding the thesis that in order to increase access to pharmaceuticals in developing countries, it is essential to choose the right view on the TRIPS Agreement and then chose the right approach for practical application that supports the chosen vision. The theoretical analysis and discussion are conducted by examining the TRIPS Agreement and Doha Declaration as well as by critically analyzing and commenting on the books and articles written by legal scholars on the similar topics.

Kehitysmaiden pääsy farmaseuttisiin tuotteisiin johtuu tiukoista patenttisuojauksista. Analysoimalla TRIPS sopimusta ja keskustelemalla sen eri tulkintatavoista, tämän tutkielman tavoite on selvittää, josko yksi ehdotetuista lähestymistavoista voisi lisätä farmaseuttisten tuotteiden saatavuutta. Tulkintatapoja ovat kansanterveyden, oikeus terveyteen sekä geneeristen lääkkeiden perspektiivit. Lähestymistavat, joita analysoidaan ovat lääkkeiden patenttipooli, avoimen lähdekoodin malli ja orpolääkkeet. Analysoinnista, josko maailmanlaajuinen lääkejärjestelmä tulisi muuttaa, keskustellaan, ennen kuin tutkielma lopettaa toteumaan, että jotta farmaseuttisten tuotteiden saatavuutta kehitysmaissa voidaan parantaa, on tärkeää valita oikea tulkintatapa TRIPS sopimuksesta ja sitten valita oikea lähestymistapa käytännön toteutukseen, joka tukee valittua näkemystä. Teoreettinen analysointi ja keskustelu on toteutettu tutkimalla TRIPS sopimusta, Dohan julistusta sekä kriittisesti analysoimalla ja kommentoimalla kirjoja ja artikkeleja samanlaisista aiheista, jotka ovat kirjoittaneet oikeustieteilijät.
Keywords: Pharmaceutical product, access, developing countries, patent protection, TRIPS